"The gratitude attitude": growing evidence for medical and veterinary professionals. Issue 5 (3rd May 2020) - Ford, Katie
ABSTRACT: Gratitude is a topic of increasing popularity across social media platforms, literature and the press. There is mounting evidence for its positive effects in mental health, physical wellbeing and creativity. Whilst specific studies in medical professionals are mostly limited to the human field thus far, there is wide scope for parallels to be drawn to veterinary practice. This article reviews recent literary findings and considers how gratitude could be implemented in the veterinary profession, both in practice and amongst individuals.